Self-Acceptance and Self Esteem on Psychological Well-Being college student raised by a Single Parent - Halim, Audrey; Setiasih , Setiasih (Syntax Literate, 2025)
This study aims to determine the effect of self-acceptance and social support on the social adaptation of children who are victims of parental divorce. This study uses a quantitative approach. The subjects of this study were 60 people, who were selected using purposive sampling technique. The data collection method used is the scale of social adaptation, self-acceptance, and social support. The collected data were analyzed by multiple regression. By using purposive sampling method, data collection in this study used a scale of social adaptation, self- acceptance and social support. The data collected was analyzed by using multiple linear regression. The results showed that: (1) there was a significant effect of self-acceptance on social adaptation with a coefficient of beta value (β) = 0.579, and t count > t table ( 4.332 > 2.002) and p value = 0.000 (p < 0.05); (2) there is a significant effect of social support on social adaptation by obtaining a beta value coefficient (β) = 0.272; t count > t table (2.261 > 2.002) and p value = 0.027 (p < 0.05); (3) there is a significant effect of self-acceptance and social support on social adaptation with a coefficient of beta (β) = 0.575, and the value of f count > f table (38,535 > 2.76) and p value = 0.000 (p < 0.05).